The effects of grazing and the meteorologic factors on wind-sand flux in the desert steppe - Meng, Biao; Gao, Cuiping; Lv, Shijie; Han, Guodong; Li, Zhiguo; Li, Junran; Wu, Qian; Zhang, Feng (Frontiers in Environmental Science, 2024)
Introduction: Affected by global climate warming and changing rainfall patterns, the degree of soil desiccation in arid grasslands has increased and soil wind erosion has become a major environmental concern. Understanding and controlling the characteristics of sand flux and wind erosion caused by the degradation of grassland vegetation, as well as their changing patterns, has become a top priority in combating grassland degradation. Therefore, the aim of this study is to clarify the extent of wind erosion in desert grasslands and its influencing factors in order to provide a theoretical basis and data support for the restoration of grassland vegetation and the sustainable development of grassland livestock production. Methods: Use of SAS and Origin statistical software to perform multifactorial analysis of variance on variables such as year, stocking rate, meteorological conditions and wind-sand flux to determine the degree of influence of different factors on sand flux and the magnitude of interactions among different factors. Results and discussion: The results showed that wind-sand flux was higher when rainfall was low and stocking intensity was high. Specifically, the wind-sand flux increased by 50.3% and 83.6% in the moderate and high grazing treatments, respectively, compared to the control. The data obtained also showed that there was a significant interaction between climate and grazing intensity, suggesting that an increase in one factor may attenuate the differences in wind-sand flux at different levels of other factors. There is likely to be a threshold effect of stocking rate of moderate grazing on the variation of wind-sand flux influenced by different factors. In summary, the factors affecting wind-sand flux in the arid desert steppe are numerous and complex, with stocking rates below moderate grazing being key to reducing wind-sand flux.